Quiz-based Learning Media - Fahreza, Fikri; Ramadhan, Rizky; Atsyani, Fathurrahman; Izzati, Nurul; Asqallani, Ibnu; Girsang, Boy Pesona Christiano (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah - 1, 2023)
Quiz-based media learning is a combination of quiz elements and information technology to create an interactive and engaging learning experience. The purpose of this journal is to explore the effectiveness of quiz-based media learning in enhancing student engagement, motivation, and learning outcomes. This journal reviews the concepts and theories underlying the use of quiz-based media learning and analyzes the factors that influence its effectiveness, including instructional design, technological aspects, and student characteristics. Successful case studies are also presented to demonstrate the success of using quiz-based media learning. Through this journal, readers will gain a better understanding of the benefits and potential of using quiz-based media learning in the student learning process. The recommendations and guidelines presented in this journal are expected to serve as a guide for curriculum developers, instructors, and educational institutions to effectively adopt and utilize quiz-based media learning in the context of higher education.